2014
DOI: 10.1039/c4nr01284d
|View full text |Cite
|
Sign up to set email alerts
|

LL37 peptide@silver nanoparticles: combining the best of the two worlds for skin infection control

Abstract: LL37-capped silver nanoparticles have antibacterial properties including inhibition of Pseudomonas aeruginosa biofilm formation, but do not affect human skin fibroblast proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 20 publications
4
51
0
1
Order By: Relevance
“…9,10 More recently, therefore, silver nanoparticles (AgNPs) have been evaluated as a safer alternative to ionic silver. 1,[11][12][13][14][15][16][17][18][19][20] The recent work from our team showed that in comparison with silver, biomolecule-coated, photochemically-produced AgNPs can have both bactericidal and bacteriostatic properties with almost negligible cytotoxic effects. 12 We also showed that oxidation of Ag to AgO is most likely the cause of the cytotoxic effects observed with AgNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 More recently, therefore, silver nanoparticles (AgNPs) have been evaluated as a safer alternative to ionic silver. 1,[11][12][13][14][15][16][17][18][19][20] The recent work from our team showed that in comparison with silver, biomolecule-coated, photochemically-produced AgNPs can have both bactericidal and bacteriostatic properties with almost negligible cytotoxic effects. 12 We also showed that oxidation of Ag to AgO is most likely the cause of the cytotoxic effects observed with AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…1,[11][12][13][14][15][16][17][18][19][20] The recent work from our team showed that in comparison with silver, biomolecule-coated, photochemically-produced AgNPs can have both bactericidal and bacteriostatic properties with almost negligible cytotoxic effects. 12 We also showed that oxidation of Ag to AgO is most likely the cause of the cytotoxic effects observed with AgNPs. 1 Our overarching goal is to expand the safe use of AgNPs in the development of implantable hybrid-biomaterials with antiinfective properties for future use as scaffolds to enable regeneration of tissue and organs at a risk of bacterial colonization and concomitant biofilm formation like diabetic foot ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…This property has been proposed as a powerful tool for photodynamic therapy (PDT), a light-mediated 20 form of clinical treatment; 4,7 (b) Silver nanoparticles (AgNP) have excellent antimicrobial properties that exceed those of silver ions themselves, and it has been proposed that the AgNP themselves are strongly anti-infective, beyond any effect due to Ag + leaching 8,9 and (c) peptides, such as LL37 can stabilize metal nanoparticles, such as AgNP, 25 while they retain their antiinfective properties and showing excellent biocompatibility. 10 Based on this observation, we present here the remarkable behavior of core-shell gold-silver nanostructures stabilized with aspartame (Asm), a common artificial sweetener. (Figure 1).…”
mentioning
confidence: 99%
“…It plays an important role in the maintenance of natural immunity, and has a direct effect on wound healing, neovascularization, and angiogenesis. 35 Chuang et al investigated whether LL37 could enhance the immunostimulatory effects of CpG oligodeoxynucleotides by increasing uptake into immune cells, thus enhancing the antitumor effects. 36 They found that treatment with the combination of CpG oligodeoxynucleotides and LL37 generated significantly better therapeutic antitumor effects and enhanced survival in tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%